Multilingval elektronisk idiomordbog - Hallsteinsdóttir, Erla (Nordiske Studier i Leksikografi, 2006)
A multilingual electronic dictionary of idioms. In this article, I present a research project on multilingual lexicography and phraseology. The aim of the project is to analyse linguistic and lexicographical theories and evaluate practical solutions in order to provide a basis for the conceptual work on and the compilation of an electronic German ø Icelandic ø Danish ø German dictionary of idioms.